Evaluation of individually body weight adapted contrast media injection in coronary CT-angiography. Issue 4 (April 2016) - Mihl, Casper; Kok, Madeleine; Altintas, Sibel; Kietselaer, Bas L.J.H.; Turek, Jakub; Wildberger, Joachim E.; Das, Marco
Abstract: Objectives: Contrast media (CM) injection protocols should be customized to the individual patient. Aim of this study was to determine if software tailored CM injections result in diagnostic enhancement of the coronary arteries in computed tomography angiography (CTA) and if attenuation values were comparable between different weight categories. Materials and methods: 265 consecutive patients referred for routine coronary CTA were scanned on a 2nd generation dual-source CT. Group 1 ( n = 141) received an individual CM bolus based on weight categories (39–59 kg; 60–74 kg; 75–94 kg; 95–109 kg) and scan duration ('high-pitch: 1 s; "dual-step prospective triggering": 7 s), as determined by contrast injection software (Certegra™ P3T, Bayer, Berlin, Germany). Group 2 ( n = 124) received a standard fixed CM bolus; Iopromide 300mgI/ml; volume: 75 ml; flow rate: 7.2 ml/s. Contrast enhancement was measured in all proximal and distal coronary segments. Subjective and objective image quality was evaluated. Statistical analysis was performed using SPSS (IBM, version 20.0). Results: For group 1, mean attenuation values of all segments were diagnostic (>325 HU) without statistical significant differences between different weight categories ( p > 0.17), proximal vs. distal: 449 ± 65–373 ± 58 HU (39–59 kg); 443 ± 69–367 ± 81 HU (60–74 kg); 427 ± 59–370 ± 61 HU (75–94 kg); 427 ± 73–347 ± 61 HU (95–109 kg). Mean CM volumes were: 55 ± 6 ml (39–59 kg); 61 ± 7 ml (60–74 kg); 71 ± 8 ml (75–94 kg); 84 ± 9 ml (95–109 kg). For group 2, mean attenuation values were not all diagnostic with differences between weight categories ( p < 0.01), proximal vs. distal: 611 ± 142–408 ± 69 HU (39–59 kg); 562 ± 135–389 ± 98 HU (60–74 kg); 481 ± 83–329 ± 81 HU (75–94 kg); 420 ± 73–305 ± 35 HU (95–109 kg). Comparable image noise and image quality were found between groups ( p ≥ 0.330). Conclusions: Individually tailored CM injection protocols yield diagnostic attenuation and a more homogeneous enhancement pattern between different weight groups. CM volumes could be reduced for the majority of patients utilizing individualized CM bolus application.